Does exposure to workplace hazards cluster by occupational or sociodemographic characteristics? An analysis of foreign‐born workers in Australia. Issue 9 (23rd June 2020) - Gosselin, Anne; Daly, Alison; El Zaemey, Sonia; Fritschi, Lin; Glass, Deborah; Perez, Elena Ronda; Reid, Alison
Abstract: Background: Disparities in exposure to occupational hazards may be linked to social position as well as the type of job a person holds. This study aimed to describe the prevalence of exposure to workplace hazards among three migrant worker groups and to assess whether social disparities in exposure for these groups remain after adjusting for occupational characteristics. Methods: Data were collected in 2017/2018 from 1630 Australian workers born in New Zealand, India, and the Philippines. Weighted estimated prevalence of exposure to 10 carcinogens and four psychosocial hazards (discrimination, job strain, vulnerability, and insecurity) was calculated for sociodemographics and occupation. Regression estimated the likelihood of exposure by sociodemographics after adjustment for occupational characteristics. Results: Exposure to workplace hazards ranged from 11.7% (discrimination) to 61.2% (exposed to at least one carcinogen). Compared with workers born in India, New Zealand born workers were over twice as likely to be exposed to diesel engine exhaust (adjusted odds ratio [aOR] = 2.60) and 60% more likely to be exposed to at least one carcinogen (aOR = 1.60) but less likely to be exposed to any psychosocial hazard. Social disparities by country of birth, sex, age, education, and number of years in Australia, as well as company size, employment type, and hours, worked remained associated with greater likelihood of reporting one or more workplace hazards after adjusting for occupational characteristics. Conclusion: Examining sociodemographic as well as occupational characteristics helps to clarify groups most likely to be exposed to workplace hazards who can be hidden when examining occupational characteristics alone.